PENGARUH PENGEMBANGAN KARIR; KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN CV SUMBER BARU NIAGA - Saluy, Ahmad Badawi; Sulistyawati, Rini (Indikator: Jurnal Ilmiah Manajemen dan Bisnis, 2017)
This research aims to analyze the influence of the employees development; compensation and working environment on performance against partial and simultaneously at CV Sumber Baru Niaga. Research design is a descriptive quantitative researchÂ  using a sample of 100 respondents as samples at the same time the population or sample is called saturated sampling. Model test using SPSS version 18.0.0.0. Test validity and reliability using Pearson Product Moment with significance level 0.05 and 0.01 multicollinearity test; with a threshold of tolerance of 0.10; test using the test of normality Kolmogorov-Smirnov. The conclusion that results obtained concludes the employee development and work environment has no significant influence on performance employees; hence the compensation and benefit has a significant influence on performance of employees. Simultaneously employee development; compensation; and work environment have a significant influence on performance of employees.